Bombesin ameliorates colonic damage in experimental colitis - (:unkn) unknown (SPRINGER, 1999)
In the present study we investigated the possible therapeutic effects of bombesin on an experimentally induced colitis model in rats. Inflammation of the colon was induced by a single intracolonic administration of 30 mg of 2,4,6-trinitrobenzene sulfonic acid (TNBS) at 8 cm from the anus. Immediately after the induction of colitis, some rats were given bombesin (10 mu g/kg; subcutaneously) three times a day for 14 days, while another group received vehicle treatment, On day 14, the rats were decapitated and plasma carbonyl content and tissue myeloperoxidase level, as an index of granulocyte infiltration into intestinal tissue, were determined in order to obtain an objective evaluation of colonic injury. In the colitis group, increased macroscopic damage score, elevated MPO level and high plasma carbonyl content, together with the microscopic appearance revealed severe inflammatory changes resembling IBD. Bombesin treatment attenuated the TNBS-induced colonic damage and stimulated histopathologically apparent mucosal proliferation, suggesting that bombesin may play a role in protecting gut integrity.
Keywords: bombesin; colon; colitis; INFLAMMATORY BOWEL-DISEASE; SMOOTH-MUSCLE CONTRACTION; ENHANCED PRODUCTION; ACTIVE DISEASE; RAT; GROWTH; INHIBITION; INTESTINE; ACID; IMMUNITY